Perbandingan Teacher Center Learning Dan Student Center Learninng Dalam Sebuah Perbelajaran - Elsa Nabila Mustofa; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
Curriculum changes in Indonesia reflect efforts to respond to the demands of current developments and educational needs. In general, changes to the curriculum are a positive step to ensure the relevance of learning to developments in society and technology. However, there are many challenges in changing the curriculum in Indonesia, such as teacher readiness, resource availability, and technology integration. The aim of this research is to find out more about the comparison of Student Center Learning (SCL) and Teacher Center Leaning (TCL) approaches in learning. The method used in this research is descriptive qualitative. The technique used was interviewing 3 teachers who taught in various schools. The results of this research are; Student Center Learning gives students an active role as developers of critical learning, while Teacher Center Learning places teachers as the main initiator. Teachers A, B, and C agree that the Student Center Learning is more interactive because it emphasizes the active role of students. They also agreed that Student Center Learning can increase students' motivation and enthusiasm for learning, because students are more involved in the learning process compared to the Teacher Center Learning (TCL) approach.